If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7z + -2z = -20 Combine like terms: 7z + -2z = 5z 5z = -20 Solving 5z = -20 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '5'. z = -4 Simplifying z = -4
| 8x-5=4+7x | | q=22-.5(20-.5q) | | 2+3(y-1)=23 | | 15=g/4=14 | | 15=g/4=1 | | x/1.4=3 | | ab=-18+48 | | 7y^2-3y=4 | | -18=-8+2y | | 6(9-2x)=-12x-18 | | 4(x-3)-7x=-18 | | 2(3y-17)=16 | | 27=2u+13 | | 9÷5/3 | | 7(m+3)=36+5m | | 158=86-v | | 9[8-(1+3r)]+12r=5(6-5r)+10r | | x/14=64 | | 8(c+3)=40 | | 106=5y+16 | | 85=9x+5x | | 180=(p)-(3p-6) | | 8w=16/5 | | x*14=64 | | (15y^2)(5y^2)Y-2/y | | t/5-3=1 | | 4x-55x=45 | | 2x/9=8 | | 2y-3=4y+8 | | (12n-n)5n= | | 22=2w-14 | | 0.8x-1=14 |